1976
DOI: 10.1126/science.1108203
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Cell-Lethal Product from the Photooxidation of Tryptophan: Hydrogen Peroxide

Abstract: Near-ultraviolet (300 to 400 nanometers) irradiation of saturated, oxygenated solutions of tryptophan in the absence of added sensitizer gives rise to substances that have various biological effects on isolated cells, including mutagenicity and selective lethality to recombination-deficient bacterial mutants. One of these biologically active products has been identified as H2O2, on the basis of spectrometric, chromatographic, chemical, and biological properties. Now H2O2 has been shown to account for the biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(31 citation statements)
references
References 10 publications
1
30
0
Order By: Relevance
“…Since light can generate hydrogen peroxide (H 2 O 2 ) in solution (Richardson, 1893; Bedford, 1927; Blum, 1932), especially in the presence of biological photosensitizers such as riboflavin, tryptophan and tyrosine (McCormick et al, 1976; Wang and Nixon, 1978), and since LITE-1 and GUR-3 are members of a gustatory receptor family, we hypothesized that C. elegans might be responding to the hydrogen peroxide generated by bright light. Using a hydrogen peroxide-sensitive electrode, we observed that light could generate hydrogen peroxide in solution that included riboflavin (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Since light can generate hydrogen peroxide (H 2 O 2 ) in solution (Richardson, 1893; Bedford, 1927; Blum, 1932), especially in the presence of biological photosensitizers such as riboflavin, tryptophan and tyrosine (McCormick et al, 1976; Wang and Nixon, 1978), and since LITE-1 and GUR-3 are members of a gustatory receptor family, we hypothesized that C. elegans might be responding to the hydrogen peroxide generated by bright light. Using a hydrogen peroxide-sensitive electrode, we observed that light could generate hydrogen peroxide in solution that included riboflavin (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…H 2 O 2 was chosen due to its capability to react with DCFH and to penetrate easily into bacteria cells35. Furthermore, H 2 O 2 is commonly accepted as one of the ROS that are generated inside bacteria under light stress36. Reaction between 10 μM DCFH and H 2 O 2 at different concentrations (0.01 to 1 mM) was done in the absence of bacteria in dark.…”
Section: Resultsmentioning
confidence: 99%
“…Irradiation by UV light generates ROS, including H 2 O 2 and superoxide ions [16, 63], which in turn induces various cellular responses in eukaryotes, including damage to DNA and proteins [64, 65], triggering of signal transduction pathways [6668], and activation of gene expression [66, 6871]. UV-B triggers the apoptotic pathway during irradiation, although the actual apoptotic process occurs later [10].…”
Section: Discussionmentioning
confidence: 99%